2022
DOI: 10.1186/s13046-022-02413-2
|View full text |Cite|
|
Sign up to set email alerts
|

Retraction Note: Knockdown of FOXO3a induces epithelialmesenchymal transition and promotes metastasis of pancreatic ductal adenocarcinoma by activation of the βcatenin/TCF4 pathway through SPRY2

Abstract: This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13046-019-1046-x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Growing evidence has mainly implied that Sprouty2 (SPRY2) as a tumor suppressor in many solid tumors, which can promote tumor cells apoptosis and inhibit their proliferation, invasion and migration ability (Sun et al, 2020;Schumacher et al, 2021). In many instances, downregulation of SPRY2 has been observed in prostate (Samadaian et al, 2018), liver (Kovi et al, 2019), lung (Yawut et al, 2020), and pancreatic cancer (Li et al, 2022), and also has been found to influence EMT process in gastric (Li et al, 2021). However, this finding is not uniformly observed across all cancer cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence has mainly implied that Sprouty2 (SPRY2) as a tumor suppressor in many solid tumors, which can promote tumor cells apoptosis and inhibit their proliferation, invasion and migration ability (Sun et al, 2020;Schumacher et al, 2021). In many instances, downregulation of SPRY2 has been observed in prostate (Samadaian et al, 2018), liver (Kovi et al, 2019), lung (Yawut et al, 2020), and pancreatic cancer (Li et al, 2022), and also has been found to influence EMT process in gastric (Li et al, 2021). However, this finding is not uniformly observed across all cancer cell.…”
Section: Discussionmentioning
confidence: 99%
“…Samadaian et al (2018) also revealed that SPRY2 inhibited cell proliferation and migration in prostate cancer cells. Li et al (2022) reported that SPRY2 was downregulated in pancreatic ductal adenocarcinoma tissues compared with adjacent normal tissues, and that SPRY2 could induces EMT and promotes metastasis by activation of the b-catenin/TCF4 pathway. Therefore, our findings suggest that SPRY2 mainly acts as a tumor suppressor, which play important role in cancer cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%